Acquired right ventricular outflow tract obstruction in twin‐to‐twin transfusion syndrome; a prospective longitudinal study. (28th November 2018) - Eschbach, Sanne J.; ten Harkel, Arend D.J.; Middeldorp, Johanna M.; Klumper, Frans J.C.M.; Oepkes, Dick; Lopriore, Enrico; Haak, Monique C.
Abstract: Objective: The pathophysiology of right ventricular outflow tract obstruction (RVOTO) in twin‐to‐twin transfusion syndrome (TTTS) recipients is incompletely understood. We aimed to investigate the development and spectrum of RVOTO in TTTS recipients. Methods: A prospective longitudinal cohort study was conducted between 2015 and 2017. Echocardiographic assessment was performed in recipients from TTTS diagnosis until the neonatal period. Results: Prenatal RVOTO, defined as abnormal flow velocity waveforms across the pulmonary valve (PV), was diagnosed in 12.9% (16/124) of recipients at TTTS diagnosis. Postnatal RVOTO was found in 6.7% (7/105) of surviving recipients. All recipients with severe postnatal RVOTO showed prenatal RVOTO at TTTS diagnosis. In 5.6% (6/108) of cases, prenatal RVOTO appeared only after laser therapy, and in 1.9% (2/108), this progressed to mild postnatal pulmonary stenosis. Elevated peak systolic PV velocities were more frequently associated with postnatal RVOTO compared with prenatal finding of functional pulmonary atresia. Postnatal RVOTO was associated with early manifestation of TTTS but was equally found in all Quintero stages. Conclusion: In the spectrum of postnatal RVOTO, severe cases show prenatal RVOTO at TTTS diagnosis. However, RVOTO can develop after laser or even in the neonatal period and in all Quintero stages. A potential risk factor for postnatal RVOTO is early TTTS manifestation. Abstract : What is already known about this topic? Postnatal RVOTO with need for surgical intervention is a potential complication of TTTS. Pathophysiology is not yet fully understood. Most studies focus on prelaser assessment of RVOTO. What does this study add? This systematic longitudinal study evaluates the development of RVOTO from TTTS diagnosis until the neonatal period to investigate the full spectrum of RVOTO and find possible risk factors.